Collaborative Approaches to Patient Data Management: A Qualitative Study on Nursing Technicians and Medical Secretaries in Saudi Arabian Hospitals - Badour Khaled Mater Almutairy,; Anifah Hammad Al Shammairy,; Mashael Munahi Almutairy,; Afaf Mourdi Hameed Almoutairy,; Eidah Mukhlef Al Anaz,; Nawaf Majed Almutairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This qualitative study aimed to explore collaborative approaches to patient data management among nursing technicians and medical secretaries in Saudi Arabian hospitals, focusing on strategies for effective communication, data accuracy, and efficiency. Methods: Semi-structured interviews were conducted with 24 participants, including 12 nursing technicians and 12 medical secretaries, working in various hospitals across Saudi Arabia. Participants were recruited using purposive sampling, and data were analyzed using thematic analysis. Results: Four main themes emerged from the data: (1) establishing clear communication channels, (2) standardizing data entry processes, (3) implementing technology-based solutions, and (4) fostering a culture of collaboration. Participants emphasized the importance of regular meetings, standardized forms and protocols, electronic health record systems, and a supportive work environment for effective patient data management. Conclusion: Collaborative approaches to patient data management in Saudi Arabian hospitals require strategies that promote clear communication, standardized processes, technology adoption, and a culture of teamwork. Policymakers and hospital administrators should prioritize these strategies to improve data accuracy, efficiency, and ultimately, patient care quality.